Perancangan Fixture Proses FreisUntukProduksi Komponen Sambungan Karburator - Prasticia Chandra Dewi (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2010)
The tools are designed to assist and simplify the machining process, and increase the number of products that can be manufactured with quality maintained. The tools aredesigned to use in the manufacture of the carburetor connection with the Freis. Freisprocess here to cut the work piece that originally shaped like a rectangle into a rhombus.The tool is made by using the principle of supporting and supported by the use ofclamping. Supporting made with a flat surface so that the entire supporting surface is assumed to touch the entire workpiece. Meanwhile, the use of bolt clamping aims to unifyworkpieces with supporting so that the workpiece can not be separated and do not moveduring the machining process takes place. This is evidenced by the equation forcesgenerated by the clamping, the force generated is positive so that the proper tool to use.With this tool, production time becomes shorter and the resulting product is also more precise so that the quality and quantity of product is assured. Production costs necessaryto complete the carburetor connection is also cheaper than without using tools.